A Field Experiment on Reducing Drinking Straw Consumption by Default - Mundt, Daria; Carl, Sebastian; Harhoff, Nico (Frontiers in Psychology, 2020)
Against the background of the pollution of the environment through plastic waste, we conducted a field experiment (N = 195) to test the effectiveness of a default nudge intervention that aimed at reducing the consumption of plastic drinking straws. We assumed that separating straws from cups by default leads to an overall decrease in straw consumption. We hypothesized that individuals would consume straws less frequently when they had to pick straws actively out of a separate straw box for their drink compared to when they could choose between cups already containing and not containing straws. Results of a logistic regression revealed a significant difference between both conditions concerning the use of drinking straws, B = 1.129 (SE = 0.30), p < .001 with an Odds Ratio of OR = 0.32. Confirming our hypothesis, results underline that minor and subtle interventions addressing waste reduction might have marked effects. More research is needed to improve current and future interventions to significantly reduce the amount of plastic consumption and consequently waste in the environment.